Evaluation of sacroiliac joint MRI for pelvic venous congestion signs in women clinically suspected of sacroiliitis. (July 2017) - Cimsit, Canan; Yoldemir, Tevfik; Tureli, Derya; Aribal, Mustafa Erkin
Background: Pelvic congestion syndrome (PCS) is a commonly overlooked condition which is a potential cause of chronic pelvic pain. Magnetic resonance imaging (MRI) of the sacroiliac joint (SIJ) may demonstrate unexpected conditions that can mimic sacroiliitis (SI). Awareness of MRI-defined pelvic venous congestion (PVC) may help in identifying PCS, where vascular abnormality may be the sole manifestation of SIJ pain. Purpose: To detect incidental MRI-defined PVC in patients who underwent SIJ-MRI for presumed SI and define the variance of its incidence. Material and Methods: A total of 870 women who underwent SIJ-MRI were retrospectively evaluated. Incidental findings of PVC and other genitourinary and musculoskeletal system disorders were documented. Results: Of the 774 included patients, 37% demonstrated incidentally detected imaging findings related to the genitourinary system, musculoskeletal system, and PVC. The prevalence of MRI-defined PVC signs was higher in patients without SI than with SI. The prevalence of musculoskeletal disorders was higher in patients with SI whereas prevalence for genitourinary disorders was similar. Binary logistic regression analysis revealed a statistically significant correlation between SI–PVC and SI–genitourinary disorders but not between SI–musculoskeletal disorders pairs ( P = 0.001, 0.001, and 0.057 > 0.05). The probability of observing SI in SIJ-MRI is positively correlated with the absence of PVC or genitourinary disorders. Conclusion: Patients who underwent MRI for presumed SI demonstrated incidental PVC as well as other genitourinary and musculoskeletal findings. An awareness of these imaging findings can help identify PVC and may draw clinicians' attention to the possibility of PCS.